Factors that influence thrift product online purchasing decisions - Walean, Ronny; Lumeno, Kimberly; Lendo, Patricia (Jurnal Mantik, 2024)
Factors that influence the decision to purchase online thrift products. The aim of this research is to find out which factors are most prominent in influencing the decision to purchase online thrift products and the data collection method is to first conduct interviews with ten people who usually shop for thrift products online and after that identify them in the sample using a questionnaire and to method analysis uses factor analysis. The factor analysis used is exploratory factor analysis. Exploratory factor analysis or main component analysis is a factor analysis technique in which some of the factors that will be formed are like determinants that cannot be determined before the analysis is carried out. From the existing results, the twenty-six statements measured can be simplified or concluded that there are three factors that are more prominent and influence the decision to purchase online thrift products